The effect of photoperiod and temperature on yield in beans - Davis, J.H.C.; Gniffke, P (International Center for Tropical Agriculture, 1983)
Photoperiod insensitivity in the germplasm collection of beans (Phaseolus vulgaris) held at CIAT is found mostly in accessions from higher latitudes. Cold tolerance is found in accessions from the high Andes, but these are all photoperiod sensitive. A break in adaptation seems to occur at about 15 degrees C, between accessions specifically adapted to cool or warm temperatures. Those adapted to cool temperatures tend to have large seeds. An attempt is being made to combine adaptation to growing and yielding at low temperature with photoperiod insensitivity. A number of breeding lines have been selected which combine improved cold temperature tolerance with photoperiod insensitivity (e.g. VRA 81078, VRA 81072). The extent to which production regions of the world can be stratified according to the optimum photoperiod/temperature response required in bean cultivars is being studied in an international phenology nursery organized collaboratively by Cornell University and CIAT. (AS)